Revisiting the role of small and medium-sized enterprises in the Malaysian economy - Hashim, Mohd Khairuddin (Malaysian Institute of Management, 2010)
Majority of the business establishments in Malaysia consist of small and medium-sized enterprises (SMEs). These enterprises operate in almost every industry. Collectively, they formed an important component of the business community in the country.Despite their important role and large numbers, limited studies have emphasized on the various contributions made by SMEs.This paper strives to provide some insights into the role and contributions of SMEs to the Malaysian economy.